PENDEKATAN BERDIFERENSIASI DALAM MODEL INQUIRY LEARNING TERHADAP PENINGKATAN HASIL BELAJAR PAI MATERI ANAK SALEH SISWA KELAS IV SD NEGERI 2 DONOTIRTO BANTUL - Yuniatun, Ismi; Asrofi, Muhammad; Amin, Lailla Hidayatul (MAMBA'UL 'ULUM, 2024)
The purpose of this class action research is to determine the improvement of PAI learning outcomes for pious children through a differentiated approach in the inquiry learning model for grade IV students of SD Negeri 2 Donotirto Bantul. Through a differentiated approach, it seeks to find out the learning needs of students to the maximum, combined with an inquiry learning model that involves students to the maximum so that students are more actively involved. This class action research was carried out in two cycles. The subject of this study is a fourth grade student of SD Negeri 2 Donotirto Kretek totaling 20 children. Data collection techniques are carried out through tests, observations, and documentation. The data analysis technique uses quantitative descriptive analysis. The results of this study show that a differentiated approach in the inquiry learning model to improve the learning outcomes of PAI material for pious children in grade IV students of SD Negeri 2 Donotirto Bantul can improve the learning outcomes of grade IV students of SD Negeri 2 Donotirto. The improvement of learning outcomes can be seen based on the value of student learning outcomes from pre-cycle, cycle I, and cycle II. This can be seen from the completeness of the first cycle which shows 65% while in the second cycle it shows a completeness of 100%, from this there is an increase in completeness of 35%.